Understanding the Barriers Towards Delivery of Patient Education and Perceptions on Health Education Delivery During Covid Pandemic among the Nurses in One of the Hospitals in Bhutan - Sangay Chozom (Journal Of Nursing Practice, 2023)
Background: Patient education is a dynamic process, including formal and informal interactive activities, which influences patients’ behavior and produces changes in knowledge, attitudes and skills for better health care outcomes. Educating patient and their relatives are a source of satisfaction for the nurses; however, they felt powerless to deliver patient education consistently due to some obstacles. Purpose: This qualitative study aims to explore barriers towards patient education among nurses and also to understand the perceptions of nurses towards patient education delivery during Covid pandemic. Methods: The study design is qualitative and the study was conducted using semi-structured interview. Recruitment of participants for the interview was based on purposive sampling techniques in order to gain broad range of perspective. Interviews were conducted with a maximum of 12 participants or until the point of saturation was achieved. Thematic analysis technique was used in order to analyze the data. Results: The findings of the study revealed that nurse related factors, patient related factors and inadequate infrastructure hindered the delivery of patient education. Only health education which required patients’ co-operation for undergoing procedure was delivered and the health education on disease condition was usually not imparted. It was also found out that the change in hospital policy during Covid pandemic has an impact on patient education delivery and that during the pandemic, Covid related education was strengthened. Conclusion: Understanding nurses’ perceptions and factors influencing the delivery of patient education may lead to information to develop strategies to promote nursing engagement in patient educational activities.